A cross-industry forum on benchmarking critical quality attribute identification and linkage to process characterization studies. (September 2020) - Demmon, Sarah; Bhargava, Swapnil; Ciolek, Doreen; Halley, Jennifer; Jaya, Nomalie; Joubert, Marisa K.; Koepf, Edward; Smith, Phillip; Trexler-Schmidt, Melody; Tsai, Philip
Abstract: Identification of Critical Quality Attributes (CQAs) and subsequent characterization in process development studies are the key elements of quality by design (QbD) for biopharmaceutical products. Since the inception of ICH Q8R2, several articles have been published on approaches to conducting CQA risk assessments as well as the application to process understanding. A survey was conducted by multiple companies participating in an International Consortium working group on the best practices for identifying CQAs with linkages to process characterization (PC) studies. The results indicate that the companies surveyed are using similar approaches/timing to identify CQAs during process development. Consensus was also observed among the companies surveyed with approaches to linkage of CQAs to process characterization studies leading to impact to control strategies and lifecycle management.